PELATIHAN WIRAUSAHA SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN GENERASI Z PADA MA BAHRUL ULUM BESUK - Fahrudin, Fahrudin; Rizal, Moh Syaiful; Dwi Supriyanto, Muhammad Sofyan; Subhan, Muhammad; Mundzir, Ali; Ghazali, M.; Zainal Abidin, Moh Ali; Alfaini, Ainul Yaqin; Shodiqin, Ghufron; Ifandi, Ifandi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Encouraging development and strengthening can be the right way to overcome generation Z unemployment, and at the same time be an important step in building a strong economy in the future. This service activity is in the form of training, which is packaged in an entrepreneurship seminar. This activity aims to provide insight and motivation for students with the hope of becoming successful young entrepreneurs and can open up job opportunities to reduce unemployment. This activity was carried out by MA Bahrul Ulum, Besuk District, Probolinggo Regency with class XII participants. The implementation method uses stages, namely the preparation, implementation, and evaluation stages, focusing on the positive impact of participation in entrepreneurship seminar training. The results of this service, the school welcomed well and the participants participated in the activities very enthusiastically during the implementation with 90% of the participants attending and the participants gaining knowledge reached 70% of the participants' understanding, to become a young entrepreneur with more confidence. The implementation of this entrepreneurship seminar training activity has a positive impact on increasing the knowledge of participants to foster an entrepreneurial spirit in themselves by holding entrepreneurial principles that are creative, always innovating, taking risks and taking responsibility. It can be concluded that this seminar activity is the first step for students in doing entrepreneurship so that it can be developed in individual knowledge and skills that can be useful for society and to create job opportunities.